Study of Spectrum lines Exposure in Magnetized Plasma using Path Integrals Formalism - Fadhel, Sara (Universty of Eloued جامعة الشهيد حمة لخضرالوادي, 2023)
In this thesis, we have found a quantum problem solution of hydrogen-like ions under a strong, nonuniform magnetic field. The intense magnetic field is the sum of two fields with toroidal and poloidal geometry, with an intensity equal to the third of the toroidal one. The results reveal the spectral line shape (Lyman-alpha) of three types of ions, He+, C5+, and Ar17+, for different magnetic field intensities. The Zeeman separation is as large as the magnetic field and charge number Z, with the left Zeeman component close to the line without a magnetic field. Then, we have calculated the hydrogen atom Feynman propagator in the non-relativistic limit where the hydrogen atoms are obeing a time-dependent electric field that complies with the Gaussian white noise statistics. Our problem turns out to be a novel Coulomb problem with a quadratic term in the lagrangian and a time-dependent coefficient. By applying some canonical transformations, a concise formula for the system's Feynman propagator was derived. في هذه الأطروحة، قمنا بحل مسألة كمومية للأيونات الشبيهة بالهيدروجين تحت مجال مغناطيسي قوي وغير منتظم.المجال المغناطيسي الكثيف هو مجموع حقلين ذي هندسة حلقية وبولويدية بشدة تساوي ثلث الحقل الحلقي. كشفت النتائج عن شكل الخط الطيفي(Lyman alpha) لثلاثة أنواع من الأيونات Ar17+وC5+،He+لشدات مجال مغناطيسي مختلفة. يكون فصل زيمان كبيرا كلما كان المجال المغناطيسي كبيرا والعدد الشحني مع كون خط زيمان الأيسر قريب من خط الطيف في غياب الحقل المغناطيسي. بعد ذلك، قمنا بحساب ناشر فاينمان لذرة الهيدروجين في ميكانيكا الكم غير النسبي، حيث تخضع ذرات الهيدروجين لحقل كهربائي يتعلق بالزمن يتوافق مع احصائيات الضوضاء البيضاء الغاوسية. تبين أن مسألتنا هي مسألة كولومب جديدة بحد تربيعي في عبارة لاغرانج وعامل تحليلي يتعلق بالزمن. من خلال تطبيق تحولات قانونية مناسبة، تم اشتقاق صيغة موجزة لناشر فاينمان للنظام.
أطروحة دكتوراه تخصص فيزياء أساسية في العلوم الدقيقة
Keywords: plasma, magnetic field, Zeeman separation, Feynman propagator, Lagrangian, Coulomb problem.; بلازما، مجال مغناطيسي، فصل زيمان، ناشر فاينمان، لاغرانج، مسألة كولومب